Impact of Instagram Usage Intensity on Self-Esteem among Preclinical Medical Students - Maria Christina Sekarlangit; Denio Adrianus Ridjab; Eva Suryani; Dwi Jani Juliawati (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Instagram is one of the social media that is growing rapidly in Indonesia. However, the impact of Instagram usage intensity, especially on the users’ emotional well-being, is still unclear. This study aimed to explore the impact of the intensity of using Instagram on the self-esteem among preclinical medical students in Jakarta.Methods: This study was an observational analytic study with a cross-sectional approach in preclinical medical students in Jakarta, Indonesia, conducted from January 2020 to January 2021. Sampling was performed by stratified random sampling followed by simple random sampling. Instagram usage intensity and self-esteem were measured using the Instagram Intensity Scale Questionnaire (IISQ) and the Rosenberg Self-Esteem Scale (RSES). Data were analyzed using the Chi-Square test.Results: Of the108 students, 45.4% had used Instagram above the usage intensity average (average 3.01), of whom 30.6% had low self-esteem (15 out of 49). There was a significant relationship between Instagram usage intensity and self-esteem (p=0.031).Conclusion: Instagram usage intensity has an impact on the self-esteem of preclinical medical students. Further studies are needed to explore this issue, as to see other contributing factors and a larger population with different characteristics.